STUDY OF POISONING DEATHS IN AND AROUND SHIMLA (H.P.) (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
A retrospective study conducted regarding poisoning cases that were reported to Forensic Medicine department IGMC Shimla in the period of last five years. Various aspects like relation with age, sex, kind of poison, hospitalization, caste and time between consumption and death were noted in 130 cases of poisoning. Male: Female ratio was found to be 1.65:1. Organophosphorus was found to be most common used poison. 66.15% were the hospitalized patients. Rajputs, being the most common of total cases and 86.92% of all were suicidal deaths.
Keywords: Poisoning; Suicidal; Organophosphorus